Polyhydroxyalkanoate (PHA): Review of synthesis, characteristics, processing and potential applications in packaging - E. Bugnicourt; P. Cinelli; A. Lazzeri; V. Alvarez (eXPRESS Polymer Letters)
Polyhydroxyalkanoates (PHAs) are gaining increasing attention in the biodegradable polymer market due to their promising properties such as high biodegradability in different environments, not just in composting plants, and processing versatility. Indeed among biopolymers, these biogenic polyesters represent a potential sustainable replacement for fossil fuel-based thermoplastics. Most commercially available PHAs are obtained with pure microbial cultures grown on renewable feedstocks (i.e. glucose) under sterile conditions but recent research studies focus on the use of wastes as growth media. PHA can be extracted from the bacteria cell and then formulated and processed by extrusion for production of rigid and flexible plastic suitable not just for the most assessed medical applications but also considered for applications including packaging, moulded goods, paper coatings, non-woven fabrics, adhesives, films and performance additives. The present paper reviews the different classes of PHAs, their main properties, processing aspects, commercially available ones, as well as limitations and related improvements being researched, with specific focus on potential applications of PHAs in packaging.